Roughness receptivity in swept-wing boundary layers – computations. (1st March 2010) - Rhodes, Richard G.; Reed, Helen L.; Saric, William S.; Carpenter, Andrew L.; , Tyler P. Neale
The crossflow instability responsible for transition over a swept wing has been found to be ultra-sensitive to micron-sized roughness at the leading edge. Transition-predictive tools are limited because of the lack of models connecting physical roughness characteristics with initial and boundary conditions needed by the computational codes. The Texas A&M Flight Research Lab (FRL) is currently conducting flight tests of a laminar flow 30° swept wing model (SWIFT – swept wing in flight tests) mounted vertically below the port wing hard-point of a Cessna O-2A Skymaster and operated at chord Reynolds numbers on the order of 7.5 million. Various roughness configurations are correlated with local skin-friction measurements downstream. As a companion to the flight experiments, the group has engaged in a computational study aimed at relating roughness features to the resulting initial amplitude of the instability. This will provide a critical connection between stability analysis design tools and transition location prediction.